2016
DOI: 10.5723/csac.2016.6.2.047
|View full text |Cite
|
Sign up to set email alerts
|

Linking Maternal Emotion Socialization to Boys' and Girls' Emotion Regulation in Korea

Abstract: This study investigated whether Korean mothers' emotion socialization beliefs are related to emotional functioning in children differing across gender. We interviewed Korean mothers (N = 100) of first graders (55 boys; 45 girls) about their sensitivity, their reactions to children's distress, and children's emotion regulation. Two components of emotion regulation were distinguished: regulation and negativity. Results revealed that mothers' proactive sensitivity and their supportive reactions were related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…In emotion socialization research, the focus is often on parents' responses to children's negative emotion, and parents who report more supportive responses in these situations have children with more emotion regulation skills, fewer conduct problems, more prosocial behavior with peers, and fewer internalizing symptoms. In contrast, nonsupportive parental responses to children's negative emotions have been associated with poorer child adjustment (Hurrell et al, 2015;Song & Trommsdorff, 2016).…”
Section: Parents' Emotion Regulation Parenting and Children's Adjustmentmentioning
confidence: 99%
“…In emotion socialization research, the focus is often on parents' responses to children's negative emotion, and parents who report more supportive responses in these situations have children with more emotion regulation skills, fewer conduct problems, more prosocial behavior with peers, and fewer internalizing symptoms. In contrast, nonsupportive parental responses to children's negative emotions have been associated with poorer child adjustment (Hurrell et al, 2015;Song & Trommsdorff, 2016).…”
Section: Parents' Emotion Regulation Parenting and Children's Adjustmentmentioning
confidence: 99%
“…As stated in the first paragraph of this section, CAN claims that cultures do not influence only the level of emotional interdependency and relatedness, but the qualities of affect regulation as well. Cross-cultural emotion socialization studies show that parents promote or inhibit different emotions of the child, depending on their cultural norms and the gender of their child (Friedlmeier et al., 2011; Song and Trommsdorff, 2016). In a way, culture influences how parents will reinforce or suppress the basic affective systems of their boys/girls.…”
Section: Cross-cultural Affective Neuroscience: How Does Culture Wirementioning
confidence: 99%
“…There may be cultural differences in how these processes operate—for example, the ways in which parents and children interact, how children express their emotions, and how parents and children alike interpret and react to each other's emotions (Emde et al., 1991; Morris et al, 2007; Saarni, 1990). In particular, studies that focus on African American (Nelson et al., 2013; Smith & Walden, 2001), Latinx (Pintar Breen et al, 2018), and Korean (Song & Trommsdorff, 2016) families have observed different distinct patterns of supportive and non‐supportive emotion socialization behaviors and associations with children's ER development.…”
Section: Discussionmentioning
confidence: 99%
“…Parents' coping with and responses to their own child's negative emotions have been identified as a key feature of the family context, because it consistently relates to children's developing ER skills and deficits (Fabes et al, 2002;Morgan et al, 2010;Pintar Breen et al, 2018;Song & Trommsdorff, 2016). Parents play an important role in emotion communication and socialization of ER skills in childhood, from the time children first begin to express their needs and desires (Eisenberg et al, 1996(Eisenberg et al, , 1998Fabes et al, 2002;Pintar Breen et al, 2018).…”
Section: Parent Responses To Emotion and Children's Emotion Regulation Developmentmentioning
confidence: 99%